PEMANFAATAN CAMPURAN ARANG AKTIF KAYU Muntingia calabura L. DAN BAKTERI Escherichia coli PADA PENGOLAHAN LIMBAH KROMIUM INDUSTRI ELEKTROPLATING - Endang Sri Lestari; Yusuf Sudo Hadi; Gustan Pari (BRIN Publishing, 2019)
The presence of heavy metal chromium wasted from electroplating industry could harm human health, such as posing cancer and kidney failure. In order to overcome this problem, the effluent treatment was carried out by means of adsorption of chromium using wood activated charcoal. This paper aims to study the benefits of Muntingia calabura wood activated charcoal, especially seeking its optimal conditions for adsorption test and the ability of Escherichia coli bacteria to turn out chromium (VI) biodegradation into chromium (III) on chromium waste of electroplating industry. Wooden charcoal was produced after heating wood at 500°C for an hour and it was activated using hot water vapor at 800°C for 70 minutes and pressure 120 mBar. The adsorption test was conducted in variation of 20−100 mg/L of adsorbate initial concentration, contact time 45−105 minutes, and stirring speed of 100−300 rpm. Biodegradation test was conducted using Escherichia coli bacteria which was incubated in nutrient broth containing of adsorption waste. Results showed that the optimal conditions of the adsorption test was recorded at the initial concentration of 70 mg/L, 150 rpm stirring speed, 75 minutes contact time, and 86.7% adsorption effectivity. The biodegradation effectivity for turning chromium (VI) into chromium (III) was recorded at 98.6%.